Model Teologi Gereja di Abad XXI: Studi Arah Pengembangan menuju Globalisasi - Harianto GP (Sekolah Tinggi Teologi Excelsius, 2019)
The model (shape, style, paradigm or style) is the most important part of seeing a development, especially the theological church. Theology here is not only interpreted as